Analisis Hukum Dan Etika Profesi Hakim Mengenai Kasus Hakim Ronald Tannur Studi Putusan Nomor 454/PID.B/2024/PN.SBY - Arenza Wahyu; Yusuf M. Said (PT. Hasba Edukasi Mandiri, 2025)
The judiciary as a symbol of the rule of law and the last bastion of justice should be impartial, and providing equal legal treatment is the desire of all levels of society This research analyzes the legal basis of decision Number 454/Pid.B/2024/PN. Sby and revealed the actions of the judge corruption case. The method used is a normative juridical approach, analyzing regulations and literature related to the perspective of Judge Professional Ethics which are the basic principles that guide the behavior of judges. The results show that there is a strong indication that the person concerned has violated the code of ethics of the judge profession as stipulated in the Code of Ethics and Code of Conduct for Judges (KEPPH). In conclusion, this policy needs to be adjusted to legal principles in terms of legal certainty, justice and utility. Its recommendations include stricter oversight to restore public confidence in the justice system and ensure that every judge's decision truly reflects justice and legal certainty.